2009
DOI: 10.1063/1.3246786
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion in organic electronic structures

Abstract: This paper presents the results of atomic force microscopy (AFM) measurements of the adhesion between materials relevant to organic solar cells and organic light-emitting devices. The adhesion is quantified using pull-off forces obtained for organic-organic, organic-inorganic, and inorganic-inorganic interfaces. The measured pull-off forces and surface parameters are then incorporated into theoretical models for the estimation of surface energies. The implications of the results are then discussed for the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…2,27,33,[43][44][45] Prior measurements of adhesion energies are presented Table II and Figure 8. These show that the computed energy release rates (Figure 8) can exceed the measured adhesion energies (Figure 7) obtained in the interfaces that are present in OLED structures.…”
Section: Modeling Of Pull-off As a Fracture Processmentioning
confidence: 99%
“…2,27,33,[43][44][45] Prior measurements of adhesion energies are presented Table II and Figure 8. These show that the computed energy release rates (Figure 8) can exceed the measured adhesion energies (Figure 7) obtained in the interfaces that are present in OLED structures.…”
Section: Modeling Of Pull-off As a Fracture Processmentioning
confidence: 99%
“…International collaborations among the United States and Africa, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] J oint US-Africa Materials Institute (JUAMI) will be held December 10-21, 2018, in Kampala, Uganda. JUAMI features tutorials on cutting-edge energy materials topics, hands-on experiments and learning activities, and research seminars.…”
Section: In Summarymentioning
confidence: 99%
“…Phase imaging, surface topography and force calibration curves were obtained for the different surfaces by AFM in contact and tapping modes to quantify the physical interaction at the polymer interface using Au-coated cantilever tips. Interaction force response between the sample and cantilever tip [32,55] was measured for each sample. The surface roughness for each surface was recorded and related to adhesion data as measured by the deflection as recorded from the interaction between Au-coated cantilever tip and the polymer surface.…”
Section: B Babatope Et Almentioning
confidence: 99%
“…Also, this type of study could be incorporated into device performance improvement studies in view of recent reported improving power conversion efficiency of conjugated polymer-based solar cells [52], which remains largely unsatisfactory for large-scale commercial production in competition with its amorphous silicon-based devices. There are indications that charge transportation at the interface could be improved by a better understanding of the physical phenomena at the interface [32]. This has brought into the fore, an intensified investigation of the physical interaction between the dissimilar materials in direct contact, which is vital to sustainable device performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation